(untitled) (The Journal of Geography Education in Africa, 2025)
Climate change has disrupted economies and continues to affect lives in several communities and countries. The United Nations Sustainable Development Goal 13.3 urges all nations to take urgent action to combat climate change. Therefore, education is crucial in promoting climate change action because it helps people reduce their impacts and empowers them to mitigate and adapt to climate change. Currently, literature on the barriers and opportunities in implementing climate change education in South African secondary schools is limited. This study is based on the teacher training conducted by Fundisa for Change using the Teaching Climate Change manual. Archer’s (1995) morphogenesis theory was used to understand the barriers and opportunities in implementing climate change education in secondary schools in South Africa. Data were gathered through document analysis and semi-structured interviews with Fundisa for Change teacher participants and with Department of Basic Education officials in Gauteng Province, South Africa, and analysed using a thematic analysis approach. The study found the following opportunities in implementing climate change education: (1) climate change topics are included in the South African national geography curriculum in the Further Education and Training phase, (2) the participating teachers exhibited adequate knowledge of environmental sustainability education, and (3) common research tasks administered require learners to apply knowledge of climate change. However, schools are supplied with lesson plans, tests, and examinations that act as barriers to implementing climate change education, hindering teachers’ agency.